1985
DOI: 10.1071/ea9850481
|View full text |Cite
|
Sign up to set email alerts
|

Beef production from three tropical grasses in south-eastern Queensland

Abstract: A grazing trial with beef cattle was conducted on three grasses, Paspalum plicatulum cv. Rodd's Bay, Brachiaria decumbens cv. Basilisk (signal grass) and Panicum maximum cv. Hamil, in the first year. P. maximum was replaced by Digitaria decumbens (pangola grass) in the second and third years. There were three stocking rates (3.0, 3.75, and 5.0 steers/ha), plots were fertilized with 300 kg N/ha, in two replicates. Animal liveweight gain was low; maximum values were 650 kg/ha for pangola grass, 640 kg/ha for sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…This expectation is supported by grazing trials that compare pasture species/composition, stocking rate and growth rates of sheep, goats and cattle; these comparisons have shown that daily and annual live weight gains from grazing B. decumbens is comparable toormayexceed growth rates on P. maximum pastures-0.46 to 0.78 kg/head/day and 0.49 to 0.61 kg/head/day, respectively [10,18,21,55,56]. Cattle in North Queensland, aged 15 months to three years of age, grazed tropical pastures including B. decumbens under a rotational grazing system at stocking rates that ranged from 0.7 to 5 head/ha [47]; annual weight gains were 211 to 950 kg/ha/year [43,47,55,57] with the highest live weight gains achieved on B. decumbens pastures. B. decumbens persist under high stocking rates and continuous grazing [55,58].…”
Section: Animal Production On B Decumbens Pasturesmentioning
confidence: 89%
See 2 more Smart Citations
“…This expectation is supported by grazing trials that compare pasture species/composition, stocking rate and growth rates of sheep, goats and cattle; these comparisons have shown that daily and annual live weight gains from grazing B. decumbens is comparable toormayexceed growth rates on P. maximum pastures-0.46 to 0.78 kg/head/day and 0.49 to 0.61 kg/head/day, respectively [10,18,21,55,56]. Cattle in North Queensland, aged 15 months to three years of age, grazed tropical pastures including B. decumbens under a rotational grazing system at stocking rates that ranged from 0.7 to 5 head/ha [47]; annual weight gains were 211 to 950 kg/ha/year [43,47,55,57] with the highest live weight gains achieved on B. decumbens pastures. B. decumbens persist under high stocking rates and continuous grazing [55,58].…”
Section: Animal Production On B Decumbens Pasturesmentioning
confidence: 89%
“…In vitro dry matter digestibility showed similar variation with early growth ranging from 56%-78% up to five weeks of age decreasing to 41.6% to 63.7% as the pasture matures [2,21,30,47,51,53,54]. The estimated nutritive value, and therefore the potential level of liveweight gain, of B. decumbens is similar to other tropical pasture species such as Panicum maximum (guinea grass), Digitaria decumbens (pangola grass) and Setaria anceps (setaria) [20,30,51,54,55]. Analytical data on chemical composition and potential digestibility (in vitro DM digestibility) of B. decumbens have shown high variability between data sets sampled through the growing period.…”
Section: Animal Production On B Decumbens Pasturesmentioning
confidence: 99%
See 1 more Smart Citation
“…Brownseed grass was initially recommended for sandy soils in Hainan (Michalk et al 1985), but commercial experiences in Queensland (Anning 1977) and more recently in China (Colman and Wolfe 1987) indicate that this grass should not be shown because it is often too competitive even for the perennial stylos and has low acceptability to cattle (Whiteman et al 1985) unless heavily fertilized with nitrogen (Yet 1980). However, even when abundant forage is available, beef output on brownseed grass pastures is very low (Whiteman et al 1985). Further, in the present study, brownseed grass did not recover from the 1983 wildfire.…”
Section: Discussion and Management Implicationsmentioning
confidence: 99%